Analysis of protection capabilities against SQL Injection attacks - Krawczyński, Bogdan; Marucha, Jarosław; Kozieł, Grzegorz (Journal of Computer Sciences Institute, 2018)
Publication refers to SQL Injection attacks whose are one of the most dangerous in a cyberspace. Based on a literature studies, classification of the SQL Injection attacks was prepared. The purpose of the work was to analyse of protections effectiveness against SQL Injection attacks. Research method has been based on author application, which was implemented in JSP (JavaServer Pages) technology using MySQL database server.